A THEORETICAL STUDY BETWEEN THE TWO ENVIRONMENTAL MANAGEMENT SYSTEMS: ECO MANAGEMENT AUDIT SCHEME –EMAS - AND ISO 14000 - BARBU, Cristina; NEGULESCU, Mihail; BARBU, Irina Catalina (Journal of Environmental Management and Tourism; Vol 3 No 2 (2012): JEMT Volume III Issue 2(6) Winter 2012, 2016)
The concept of an environmental management system evolved in the early nineties. An environmental management system exists to help organizations minimize how their operations (processes etc.) negatively affect the environment (i.e. cause adverse changes to air, water, or land), comply with applicable laws, regulations, and other environmentally oriented requirements, and continually improve in the above. An environmental management system can also manage natural resources, and improve the reliability and credibility of the environmental policies. At the European level we have EMAS. The Eco-Management and Audit Scheme (EMAS) is the EU’s voluntary scheme designed for companies and other organisations committing themselves to evaluate, manage and improve their environmental performance. This was introduced by a European Union council regulation (No. 1836/29.06.1993), requiring implementation in all European Union Member States. EMAS was formally introduced in the United Kingdom in April 1995. ISO 14000 is an International Standard (1996) Applicable on an international scale. This paper aims to make a theoretical comparison between these two environmental management systems.
Keywords: environmental management system; EMAS; ISO 14000; European Union